Pay What You Want as A Pricing Model for Open Access Publishing? - Martin Spann; Lucas Stich; Klaus M. Schmidt (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2017)
We analyze "Pay What You Want" as a business model for Open Access publishing by discussing motives leading authors to make voluntary contributions, potential benefits for publishers and present results from a field experiment at one publisher. Data from the field experiment indicate authors' willingness to voluntarily contribute.
Keywords: M31; D03; L11; 330; Gold open access; article processing charges; customer-driven pricing; voluntary contributions; field experiment